2005
DOI: 10.1108/03074800510635008
|View full text |Cite
|
Sign up to set email alerts
|

The necessity of information literacy education in a marketing department

Abstract: Purpose -To provide reliable data for the development of efficient information literacy education in a department of a higher educational institute in Thessaloniki, Greece. It requires in-depth understanding of the current situation as well as future expectations. Design/methodology/approach -Two research objectives were set. One was to record the use of resources by students and their perceptions, as well as the expectations of faculty regarding information literacy skills. The other was to examine the prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…A study done by Lee and Read (1972) revealed that among graduate business students who had taken a business research course, two-thirds rated their research ability good to excellent while one-third rated it poor to very poor; in those that had not taken the course these proportions were reversed. Korobili and Tilikidou (2005) found that the use of library resources by Greek marketing students is correlated with prior attendance at a library-research class. Prince and Helms (1993) concluded that an integrated library instruction session reduces library anxiety, increases students' ability to use library resources, and strengthens the relationship between library staff and students.…”
Section: Library Instruction For Business Studentsmentioning
confidence: 96%
“…A study done by Lee and Read (1972) revealed that among graduate business students who had taken a business research course, two-thirds rated their research ability good to excellent while one-third rated it poor to very poor; in those that had not taken the course these proportions were reversed. Korobili and Tilikidou (2005) found that the use of library resources by Greek marketing students is correlated with prior attendance at a library-research class. Prince and Helms (1993) concluded that an integrated library instruction session reduces library anxiety, increases students' ability to use library resources, and strengthens the relationship between library staff and students.…”
Section: Library Instruction For Business Studentsmentioning
confidence: 96%
“…In addition three surveys have been undertaken to map the situation in Greece. The first survey addressed students and faculty of the Marketing Department of TEI (Korobili and Tilikidou, 2005). The project revealed that a small percentage uses electronic library resources, especially those in their first semesters.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Our research and the literature highlighted the limited referencing requirements in Greek undergraduate education (Korobili & Tilikidou, 2005;Katsikas, 2009), as Katsikas (2009) notes "Greek students are unaware of the concepts of reference sources and related literature. "Additionally, whilst recent changes to Greek libraries (especially since 2002) have provided access to electronic journals (Xenidou-Dervou, 2003), as the language of instruction is Greek, referring to other sources (outside of the textbook) is difficult as there are limited numbers of academic publications written in Greek.…”
Section: Information Literacymentioning
confidence: 95%
“…Korobili, Malliari, and Christodoulou (2009) also found that a good percentage of staff at this Greek higher educational institution "was not acquainted with electronic sources (p.341)" and that faculty tended not to motivate students to use library sources (Korobili & Tilikidou, 2005;Birk and Karageorgiou (1993). This lack of experience with regard to information literacy could be explained as being due to the reliance on textbooks and also the fact that most Greek faculty do not require students to undertake individual coursework (Korobili & Tilikidou, 2005). Finally, Korobili et al (2009) note that there has been a paucity of the literature pertaining to the information literacy in Greek universities.…”
Section: Information Literacymentioning
confidence: 95%
See 1 more Smart Citation